Analysis of Dispute Resolution towards Overlapping Ownership of Land Rights in South Konawe District - Jumiati Ukkas; Amelia Agustin Nur Fatimah; Muh. Rizky Anshary; Muh. Soelaiman Purnama Kaimuddin (Journal of Law, Social Science and Management, 2025)
Background: Disputes over overlapping land rights ownership are a complex and frequent issue in Indonesia, including in South Konawe. This journal analyzes the settlement of these disputes by examining various factors that affect land rights, such as legal regulations, government policies, and social and economic dynamics of the local community. Objective: this paper aims to analyse several factors that cause land disputes and legal resolution models for overlapping land ownership conflicts. Methods: The analysis method used includes case studies of disputes that occurred in South Konawe, interviews with related parties, and review of legal documents. Result: The results of the analysis show that, one, causes and impacts of land disputes. Two, the resolution of disputes over overlapping land rights ownership in South Konawe requires a comprehensive approach, involving mediation, community participation, and firm law enforcement. It is hoped that this article can provide insight for stakeholders in formulating effective strategies to resolve land disputes in the area. Conclusion: This land dispute includes social instability, economic losses, and human rights violations. Resolution of overlapping land ownership disputes can be achieved through litigation and non-litigation methods. To ensure legal certainty over land rights, cooperation between the government, society, and the private sector is needed to create a better land system. Socialization about land rights and a deeper understanding of the law for the community will be very helpful in preventing disputes in the future. Keyword: Dispute Resolution, Overlapping Land, Social Conflict, Litigation, nonlitigation